Evaluation of treatment in AGE: A comparative study - Gulsen Yalcin; Fatma Demirbas, Fatma Bacalan; Evin Bahar Toy (Journal of the Pakistan Medical Association, 2022)
Objective: Acute gastroenteritis (AGE) is one of the most common infections among children. Oral rehydration is the first-line treatment. In this study, it was aimed to compare the efficacy of probiotics, zinc, and combined therapies in children admitted with AGE. Methods: The study included 132 patients with a diagnosis of AGE in the Pediatric Emergency Service between October 2020 and April 2021, in a comparative study, prospective, placebo-controlled manner. Only appropriate dietary recommendations were given to the first (control) group, probiotics (Bifidobacterium breve, Bifidobacterium bifidum, Bifidobacterium infantis, Bifidobacterium longum) to the second group, zinc to the third group, and probiotics and zinc to the fourth group.1. Results: A total of 132 participants (27.5 ± 3.6 months, 59.8% male) were included in the study. The mean duration time of the termination of diarrhea was 84.5 ± 10.7 hours (range; 79-89) in group1, 73.05±6.8 hours (range; 70.5-75.4) in group 2, 80.1 ± 10.3 hours (range; 76-84) in group 3, and 43.5±9.6 hours (range; 46-48) in group 4. When all groups were compared, the duration of the termination of diarrhea was shorter in group 4 with a statistically significant level (p<0.001). Conclusions: Our study showed that in the management of acute diarrhea, the efficiency of combined treatment with probiotics and zinc was better than other treatments. New studies are needed to be able to use this combination together in the treatment of childhood AGE. Keywords: Child, Gastroenteritis, Probiotic, Zinc